Influence of the Severity of Osteogenesis Imperfecta on Cranial Measurements - Manuel Joaquín De Nova-García; Rafael G. Sola; Laura Burgueño-Torres (MDPI AG, 2023)
Osteogenesis Imperfecta (OI) is a disease that causes bone fragility and deformities, affecting both the cranial base and the craniocervical junction, and may lead to other neurological disorders. A retrospective cross-sectional study was carried out based on cephalometric analysis of the cranial base in a sample of patients with OI, in lateral skull radiographs and magnetic resonance imaging (MRI), comparing them with a sample of age-matched controls. When the different variables of the craniocervical junction were analyzed, significance was found in comparisons with the different age groups. All measurements of the variables studied stabilized as growth progressed. For most of the variables, the severity of the disease influences the measurements of the skull base, with statistically significant differences. Both age and severity of the disease are factors that directly influence the anatomy of the craniocervical junction in these patients and may serve as indicators in the early detection and prevention of other derived alterations.